A Hebrew Echo of Catullus’ Passer circa 1400? - Gutwirth, Eleazar (Rassegna Iberistica, 2018)
Against the background of a long standing tradition which sees the Hispano-Jewish culture of the late Middle Ages in terms of decline and isolationism, the article attempts to analyse – and argue for an echo of Catullus’ Carmina in – a Hebrew poem of the Catalano-Aragonese “guild of the poets”. It tries to contrast the unverified attributions of translations from the Latin or the putative existence of romance texts which have not been found with the close analogy of themes and motifs between the Hebrew and the Latin poem. It contextualises it in the frame of other cultural manifestations of close contacts between Jews and Christians as well as the rich evidence of the archival documents of the fourteenth and fifteenth centuries.